ANALISIS BIBLIOMETRIK : LAYANAN PERPUSTAKAAN TERHADAP PENYANDANG DISABILITAS KOGNITIF - Dhinosa, Elvaretta Vito Dhinosa; Faizah, Putri Nurul (UIN Imam Bonjol Padang, 2024)
This study analyses trends in scientific publications related to library services for people with cognitive disabilities through a bibliometric approach. Data was retrieved from Google Scholar using a combination of relevant keywords, covering the period 2020-2024. The results of the analysis show an increase in publications in 2020 due to the COVID-19 pandemic, which drives the need for adaptive technology to support accessibility. However, this trend experienced a sharp decline in the following years. Wiley Online Library emerged as a major publishing platform with significant contributions to the literature in this field. In addition, analysis of author productivity and relationship strength showed that strategic collaboration has a significant impact on research influence. This research provides important implications for the development of more inclusive library services, especially for people with cognitive disabilities. Utilization of participatory designed technology and diversification of publishing platforms are key recommendations. For future research, it is recommended to focus on longitudinal analysis, adaptive technology development, and exploration of the specific needs of this disability group. It is hoped that this research will provide a solid foundation for improving the accessibility and inclusiveness of library services globally.